Change Your Diet: How CO 2 , Plant Phenology and Genotype Alter Grapevine Quality and Affect Performance and Larval Transcriptome of an Insect Herbivore - Christine Becker; Christof B. Steingass; Heiko Vogel; Annette Reineke (Molecular Ecology, 2025)
Herbivorous insects need to cope with changing host plant biochemistry caused by abiotic and biotic impacts, to meet their dietary requirements. Larvae of the multivoltine European grapevine moth Lobesia botrana , one of the main insect pests in viticulture, feed on both flowers and berries. The nutritional value and defence compounds of these organs are changing with plant phenology and are affected by climate change which may accordingly alter plant–insect interactions. Here, we assessed the impacts of future elevated atmospheric CO 2 concentrations on the host plant quality of different grapevine organs and the larval performance and the transcriptome of L. botrana . Using the Geisenheim VineyardFACE facility, where ‘Riesling’ and ‘Cabernet Sauvignon’ were cultivated in the field under ambient or elevated (ca. + 20%) atmospheric CO 2 concentrations, we found that nutrient (amino acids and sugars) and defence compound (phenolic compounds) concentrations of inflorescences and ripening berries differed strongly due to plant phenology and less due to cultivar and CO 2 concentration. Assessing global gene expression after feeding on the respective organs, we found that larval transcriptomic plasticity largely mirrored the plant biochemical plasticity. Larval relative growth rate differed between treatments in a plant phenology‐dependent manner. Grape berries contained higher amino acid concentrations and altered phenolics profiles after larval feeding. In the near future, the grapevine– L. botrana interaction will probably change less because of elevated CO 2 concentrations than it does currently during one season. Changes associated with plant phenology, however, may be relevant for contemporary pest management.